Effects of irrigation and rootstock on Vitis vinifera (L.) cv. Shiraz berry composition and shrivel, and wine composition and wine score. (7th October 2015) - Stevens, R.M.; Pech, J.M.; Taylor, J.; Clingeleffer, P.; Walker, R.R.; Nicholas, P.R.
Abstract: Background and Aims: We investigated rootstock effects on the response of fruit and wine composition to reduced irrigation in vines growing on saline soil. Methods and Results: Drip‐irrigated Shiraz vines on five rootstocks were subjected to industry standard and 30% reduced irrigation over four consecutive seasons. Fruit composition during berry shrivel and at harvest was assessed in each season and wine was made and assessed in two seasons. Rootstock and irrigation independently affected fruit anthocyanins concentration and wine spectral properties. In two seasons, reduced irrigation affected the accumulation of anthocyanins and total soluble solids during berry shrivel. Fruit from 110 Richter had a 16% higher concentration of anthocyanins and wine a 29% higher colour density than that of fruit and wine from Ramsey. Sodium and chloride concentration in wine from 110 Richter was 27 and 50% less than in wine from Ramsey. In one of two seasons, reducing irrigation improved the sensory score from wines on 110 Richter and 140 Ruggeri rootstocks. Yield and berry mass accounted for 25% and less than 1%, respectively, of the variation in concentration of fruit anthocyanins over four seasons. Conclusion: Reducing irrigation and substitution of 110 Richter for Ramsey rootstock both improved fruit composition, but reduced yield. In the early 2000s, the extra payment for higher quality did not offset the loss due to lower yield. Significance of the Study: Wine from vines on 110 Richter had higher colour and a lower concentration of sodium and chloride than that wine from vines on Ramsey.